(untitled) (UNED Research Journal, 2026)
Introduction: One of the main concerns in current agricultural systems is the decline in soil quality and the deterioration of ecosystem services, highlighting the need to recover ancestral agricultural practices such as cover crops, which combine improvements in production systems with climate change mitigation. Methods: This literature review analyzes 111 publications from 2010 to 2025, examining the effects of cover crops across four thematic areas: (1) soil conservation and physical properties, (2) organic matter and nutrient inputs, (3) soil ecology, and (4) climate change mitigation. Results: Cover crops enhance soil structural stability, increase porosity, and promote greater water infiltration, thereby reducing water erosion. They also contribute biomass and nutrients that enrich organic matter, improve fertility, and strengthen moisture retention, even under hot conditions. Ecologically, they diversify soil biota, stimulate microbial and macrofaunal communities, and promote beneficial associations such as mycorrhizae. They represent a valuable strategy against climate change by enhancing carbon sequestration and reducing reflected solar radiation. However, living cover crops remain underutilized, mainly due to limited research on their integration into conventional agricultural management plans. Conclusion: Current literature indicates that cover crops are a key alternative for addressing agricultural challenges, helping to curb soil degradation and serving as a natural climate solution through carbon sequestration and radiation reduction. Nevertheless, their adoption remains limited, hindering the alignment of agricultural production with resource conservation and the development of more resilient and sustainable agroecosystems.